Establishing Joint Orientation Angles of the Limbs in Korean Raccoon Dogs (Nyctereutes procyonoides koreensis) Using Computed Tomographic Imaging - Seongju Ko; Sangjin Ahn; Ho-Hyun Kwak; Heung-Myong Woo; Junhyung Kim (Animals)
Studies are being conducted on the anatomical structures of various wild animals. Despite the ecological importance of the Korean raccoon dog (Nyctereutes procyonoides koreensis), limited research has been conducted on its anatomical structure. This study is the first to establish a reference range for joint orientation angles in the limbs of the Korean raccoon dog. Joint orientation angles are an unexplored concept not only in Korean raccoon dogs but also in other wildlife. However, they are important in the examination of the skeletal anatomy of humans and companion animals, such as dogs and cats. Because this type of measurement is still emerging in wildlife research, we applied the methodology used in the domestic dog (Canis lupus familiaris). Angles were measured between the mechanical or anatomical axis and the joint orientation lines in the thoracic and pelvic limbs of Korean raccoon dogs. No significant differences were observed between the sexes or between the left and right sides. These findings are consistent with those observed in domestic dogs. Based on this study, a reference range of joint orientation angles could be established for Korean raccoon dogs.